Hubungan antara harapan dan kualitas hubungan pada dewasa muda yang sedang menjalani hubungan pacaran - Indrawati, Fenny; Sani, Riryn; Ariela, Jessica (Konsorsium Psikologi Ilmiah Nusantara, 2018)
Dating is an exclusive relationship between an individual and his or her partner. This romantic relationship is of great importance for individuals in early adulthood. Furthermore, recent studies found that related problems in dating can decrease an individual's mental health. Therefore, individuals need high hope to effectively resolve conflicts and maintain the relationship well. While going through a romantic relationship, individuals can evaluate their relationships positively or negatively, termed as relationship quality. This study aims to examine whether hope correlates with relationship quality on 200 young adults who are currently in a dating romantic relationship. The present study is a quantitative study using The Hope Scale and The Perceived Relationship Quality Component as measuring instruments. The result shows that there is a significant relationship between hope and relationship quality. In other words, with higher hope, relationship quality will be higher, and vice versa. Other related findings are discussed.